A Field Study of Chinese Migrant Workers' Attitudes toward Risks, Strategic Uncertainty, and Competitiveness - Li Hao; Daniel Houser; Lei Mao; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2014)
Using a field experiment in China, we study whether migration status is correlated with attitudes toward risk, ambiguity, and competitiveness. Our subjects include migrants and non-migrants. We find that, migrants exhibit no differences from non-migrants in risk and ambiguity preferences elicited using pairs of lotteries; however, migrants are significantly more likely to enter competition in the presence of strategic uncertainty when they expect competitive entries from others. Our results suggest that migration may be driven more by a stronger belief in one's ability to succeed in an uncertain and competitive environment than by risk attitudes under state uncertainty.
Keywords: C93; D03; D63; J61; 330; migration; risk preferences; strategic uncertainty; ambiguity; field experiment